RELIABILITY ASSESMENT SISTEM DISTRIBUSI 20 KV DI PT PLN (PERSERO) ULP MOJOAGUNG MENGGUNAKAN MARKOV MODEL - Erine Puspita Sari; Enrico; Imron Ridzki; Kumala Mahda Habsari (Politeknik Negeri Malang, 2021)
The Markov Model analysis is a special probabilistic model commonly called a Stochastic process or a probabilistic change process that occurs continuously. This method is used to analyze the likelihood of disturbances occurring in the following year (2021 and 2022). The reliability of the feeder is assessed based on the duration and frequency of disturbances. The analysis process refers to feeder disturbance data from 2018-2020 using the Markov Model. The results of the analysis are used to determine efforts to improve feeder reliability. In 2021, it is estimated that 70.59% of Mojolegi Feeders will experience disturbances every month with 29.41% of level G disturbances. Meanwhile, in 2022, the percentage of disturbances increased by 1.07% from the previous year with a level G disturbance of 28.63%. This indicates that the Mojolegi Feeder is still prone to disturbances and experiences an increase in disturbance percentage every year. In 2021, it is estimated that 11.43% of Gading Feeders will experience disturbances every month with 25.00% of level G disturbances. Meanwhile, the percentage of disturbances in 2022 is consistent at 11.43% with a level G disturbance of 25.00%. This indicates that the Gading Feeder is still within the safe corridor of disturbances and experiences a constant value every year. From the analysis results, areas prone to disturbances with their causes are obtained. In response to this, PT PLN (Persero) ULP Mojoagung can focus on maintaining the distribution network in areas prone to disturbances. Efforts to improve the reliability of the Mojolegi Feeder can be focused on section V, while efforts to improve the reliability of the Gading Feeder can be focused on section II. This aims to improve feeder reliability at PT PLN (Persero) ULP Mojoagung.